Consecutive Affinity and Ion-Exchange Chromatography for AAV9 Vectors Purification - Ozgun Firat Duzenli; George Aslanidi (Biomedicines)
Background: Irrespective of the rapid development of AAV-based gene therapy, the production of clinical-grade vectors has a bottleneck resulting from product-related impurities such as empty and partially filled capsids, which lack a functional recombinant genome. Methods: In the current study, we applied the sequential affinity chromatography (AC)- and anion-exchange chromatography (AEX)-based method for purification of AAV9 vector harboring single-stranded genome encoding the fusion of firefly luciferase (fLuc)-yellow fluorescent protein (YFP) under chicken beta actin (CBA) promoter. We assessed the efficiency of two different pre-packed cross-linked sepharose and one monolithic AEX columns following AC purification to separate fully encapsulated with recombinant DNA AAV vectors from byproducts. Results: We showed the possibility to achieve approximately 20–80% recovery and over 90% calculated DNA-containing/empty capsid ratio depending on column and buffers composition. Additionally, we confirmed the infectivity of AAV by in vitro luciferase assay regardless of recovery method from different AEX columns. Conclusions: Our purification data indicate the effectiveness of dual chromatography method to obtain rAAV9 vectors with DNA-containing capsid content over 90%.